The Implementation Of Halal Product Guarantee System For Self-Declare Halal Program In Frontier, Outermost and Least Developed Regions - Akbarizan, Akbarizan; Hertina, Hertina; Murhayati, Sri; lestari, fitra lestari (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
The program of self-declare halal certification by the Indonesian Government can increase the community's life level. Self-declare halal can increase people in business sales for the global market and improve the community business unit. In this case, guidance and companion strategy are required until the business actor can obtain halal certification. The data were collected on 20 business actors of MSME in Rupat Island, Bengkalis Regency, using Strategic Assumption Surfacing and Testing (SAST) with five indicators covering the commitment and responsibility, material, halal product process, the product, and monitoring and evaluation. The research results showed that the commitment and responsibility indicator is the highest indicator, becoming the priority of companion module proposal making of halal certification at 3T Areas (Least Developed, Frontier, and Outermost) Regions. Further research needs to identify the success factor of the business actors in 3T regions in gaining the halal certification program from the Government.